Faktor-Faktor yang Berhubungan dalam Pengelolaan Obat atau Obat Tradisional untuk Pengobatan Sendiri di Masa Pandemi - Melviani Melviani; Rohama Rohama (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Self-medication or self-medication is the activity or act of self-medicating with medication without a proper and responsible prescription. Limited activities and activities caused by the COVID-19 pandemic eventually led to limited health care activities. People who have complaints of pain feel more vigilant to check the situation to medical personnel so choose to do the independent treatment. The purpose of this study is to find out the factors that affect the management of traditional drugs and drugs independently in the covid-19 pandemic. This research is descriptive. The sample in this study amounted to 113 people with convenience sampling techniques. The results obtained based on research are known that the management of drugs and traditional medicines independently is influenced by gender, occupation, and distance of the place to buy, based on statistical tests of factors that affect drug management both before the pandemic and after pandemic obtained a value of p 0,000 (<0,05), which means there is a meaningful relationship between drug use both before the pandemic and after the pandemic with gender, work, and the distance from where to buy.